Solving 0-1 knapsack problems by a discrete binary version of cuckoo search algorithm. (1st January 2012) - Gherboudj, Amira; Layeb, Abdesslem; Chikhi, Salim
Cuckoo search (CS) is one of the most recent population-based meta-heuristics. CS algorithm is based on the cuckoo's behaviour and the mechanism of Lévy flights. Unfortunately, the standard CS algorithm is proposed only for continuous optimisation problems. In this paper, we propose a discrete binary cuckoo search (BCS) algorithm in order to deal with binary optimisation problems. To get binary solutions, we have used a sigmoid function similar to that used in the binary particle swarm optimisation algorithm. Computational results on some knapsack problem instances and multidimensional knapsack problem instances show the effectiveness of the proposed algorithm and its ability to achieve good quality solutions.